Frequency of a Vanderpol oscillator with large cubic restoring nonlinearity - Dinh, Nguyen Van; Tri, Tran Duong (Vietnam Journal of Mechanics, 2003)
In [2], a modified Poincare method has been presented and applied to evaluate the period (frequency) of free oscillation in an undamped Duffing oscillator with large cubic restoring nonlinearity. There, the system examined is supposed to be near certain linear one with unknown (to be evaluated) frequency.